The Use of bioimpedance in renal problems and monitoring for volume analysis: A literature review (2024)
Abstract - Chronic Kidney Disease (CKD) constitutes a significant public health challenge due to its high prevalence and serious implications for patients’ health. In this context, bioimpedance stands out as an emerging tool with great potential for early detection and continuous monitoring of CKD. Through a systematic review based on the Scopus database and following a methodology adapted from PRISMA, this analysis delves into the use of BIA to assess hydration status in individuals affected by CKD. The meticulous search resulted in the identification of 458 relevant publications, including 23 reviews, 22 conference papers, and 1 editorial letter, highlighting a predominance of observational studies (85%) compared to randomized controlled clinical trials (15%). This research highlights a notable increase in interest and research into bioimpedance and CKD, particularly evident since 2019. Bioimpedance is validated as well as a valuable tool for accurate assessment of hydration in CKD patients, calling attention to the imperative for further research to consolidate its utility in early detection and effective monitoring of this critical condition.